The Protection of the Environment in Regional Human Rights Systems Outside of Europe II: The African Human Rights System - Mensah, Cocou Marius (Human Rights and Environmental Protection from a Central and Eastern European Perspective, 2026)
The increasing recognition of environmental protection as a human right, as demonstrated by the United Nations General Assembly’s 2022 adoption of the right to a clean, healthy, and sustainable environment, reflects the vital connection between environmental sustainability and the fulfilment of basic human rights. This chapter explores the role of the African human rights system in enforcing environment-related human rights, with particular focus on Article 24 of the African Charter on Human and Peoples’ Rights (ACHPR). Despite Africa’s minimal contribution to global carbon emissions, the continent suffers disproportionately from the impacts of climate change. However, landmark cases concerning environmental protection have been scarce in Africa’s regional human rights system, with national and sub-regional courts taking the lead in adjudicating environmental disputes. This research highlights the challenges and opportunities for African human rights institutions in addressing environmental harm and promoting the right to a healthy environment.